Porous structure of carbon-based materials studied by means of X-ray small angle scattering method - Venhryn, B.Ya.; Grygorchak, I.I.; Kulyk, Yu.O.; Mudry, S.I.; Shvets, R.Ya. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The porous structure of carbon-graphite materials: styrene-divinylbenzene copolymer (SBC) and fruit stones (FS) has been studied by means of X-ray small angle scattering method. The angular dependences of scattered intensities have been obtained and analyzed by means of the Guinier method. The main parameters of porous structure have been determined (inertia radius, pore size distribution functions, specific surface areas).
Optica Applicata, Vol. 38, 2008, nr 1, s. 119-125
Keywords: optyka; nanoporous carbon; porous structure; specific area; X-ray small angle scattering